Nationsbildung als "kulturelle Luege" Eine vergleichende Untersuchung zur kroatischen und tschechischen nationalen "Wiedergeburtsbewegung" des 19. Jahrhunderts - Zoric, Andreja (Slavistische Beitraege, 2005)
Based on the fact that nations are not natural facts but constructive communities, in this work the nation-building processes of Croats and Czechs, who were resurrected in the 19th century, are studied in literary and cultural semiotics. In the foreground next to the comparative aspect is the question of the constructedness or even the lewdness of the two reincarnation processes. To evaluate the constructive character of cultural inventions or innovations, the author develops the concept of successful or unsuccessful cultural lies. By means of this distinction, she succeeds in classifying the respective national self-description models in terms of their functionality and attractiveness